PENERAPAN PEMBELAJARAN GENERATIVE LEARNING MODEL UNTUK MENINGKATKAN HASIL BELAJAR KOMPETENSI DASAR MENDESKRIPSIKAN KONDISI FISIK WILAYAH DAN PENDUDUK PADA SISWA KELAS VIII SMP NEGERI 1 MANGARAN - Lusi Endang Sri Darmawati (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2015)
Applied learning models generate less teacher student learning outcomes is the use of leaning methored while following learning activies. The purpose of this research is to improve student learning outcome through yhe application of generative learning model in social in cocial studies with basic competencies describe the physical condition, region. Indonesia’s population in order to improve student learning outcomes on Class VIII-C State Junior High School 1 Mangaran. The object of this research wasstudents of Class VIII-C as many as 31 students. The design of this study used four phases, planning, action, observation and reflection. To obtain the data, this study usedobservation, interviews and tests. The results which obtained in this study showed an increase in student learning outcomes. At the level of achievement of pre-cycle mastery clasic obtained by 77%, with the act of learning in the first cycle occurred an increase learning outcomes by 7% with classical mastery percentage of 84%, 26 students who completed and 5 studets are still not finished. While improving learning outcomes cecond cycle of 3% and mastery learning students in the classical is 87% which is the number of students who comleted study as many as 27 students and 4 students not yet complete. Thus the application of generative learning model can improve student’s learning outcomes in the Class VIII-C State Junior High School 1 Mangaran.